Figurativeness in competing geopolitical discourses: the U.S. and Russian narratives in and on Africa - (:unkn) unknown (My University, 2023)
Historically, Africa has been a battleground for geopolitical, ideological and economic competitions between great powers (Weise and Macaulay 1985, Bonnier and Hedenskog 2020). This study focuses on the revival of the geopolitical struggle in Africa between the U.S. and Russia (Stronski 2019, Cohen 2020), notwithstanding the denial of the American Secretary of State Anthony Blinken during his visit to South Africa: “And our commitment to a stronger partnership with Africa is not about trying to outdo anyone else. We’ve all heard that narrative, that South Africa and the continent as a whole are the latest playing field in the competition between great powers. That is fundamentally not how we see it.”The analysis relies on both Critical Discourse Studies (CDS) and analyses in Cognitive Linguistics (Thompson 1988, Fairclough 1992, van Dijk 1995, Chilton and Lakoff 1995, Reisigl and Wodak 2009, among others). It investigates the speeches given by the Russian Foreign Minister Sergey Lavrov (12,821 tokens) and the U.S. Secretary of State Anthony Blinken (14,830 tokens) during their respective visits to Africa in July and August 2022. The corpus-based analysis seeks to understand how the two antagonists combine various discursive constructions and strategies with figurative language (Chilton and Lakoff 1995 and Twardzisz 2011) to sustain and convey the narratives and the international agenda of their countries. The findings reveal that the two diplomats extensively conceptualize (metonymically and metaphorically – see Kövecses 2003) Africa as a key geopolitical FRIEND or PARTNER. The ultimate goal of these conceptualizations is to foreground their own ideologies in order to tighten their “special” relationship with Africa. We also examine the socio-cognitive effects of the discourses on the African leaders and people. The study of a sample of reactions and counter-discourses shows that the geopolitical and ideological subordination of African n
Keywords: African Research